2004
DOI: 10.1002/lsm.20004
|View full text |Cite
|
Sign up to set email alerts
|

Chronic UVB exposure enhances in vitro percutaneous penetration of 5‐aminulevulinic acid in hairless mouse skin

Abstract: The stratum corneum barrier function is less effective in chronically UVB-exposed skin than in normal non-exposed skin, but more effective than in tape stripped skin. A higher penetration rate of ALA into (pre)cancerous lesions may be (partly) responsible for the greater accumulation of PpIX in such lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…In contrast to the previous finding that basal TEWL in photo-aged skin is similar to that in non-photoaged subjects aged 80-97 years [29] , the present studies demonstrate that daily sun exposure does induce dosedependent changes in basal TEWL, which is in agreement with previous findings [40] . The different results may be due to the subjects' ages.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast to the previous finding that basal TEWL in photo-aged skin is similar to that in non-photoaged subjects aged 80-97 years [29] , the present studies demonstrate that daily sun exposure does induce dosedependent changes in basal TEWL, which is in agreement with previous findings [40] . The different results may be due to the subjects' ages.…”
Section: Discussioncontrasting
confidence: 57%
“…In consistence with our previous work, MAL-induced PpIX fluorescence was higher in UV-exposed skin compared with non-UV-exposed skin (6). We consider this is most probably explained by increased MAL penetration in chronically UV-exposed skin due to altered stratum corneum barrier (7). However, epidermal hyperplasia may also contribute to enhanced PpIX formation, as it is well known that UV exposure induces epidermal hyperplasia (8).…”
Section: Funding Supportsupporting
confidence: 86%
“…Van den Akker et al . () found that chronic UVB‐exposure induced changes in the mouse skin that resulted in a 10‐fold increase of percutaneous penetration for 5‐aminolevulinic acid compared with normal mouse skin. This increase is still less than through tape‐stripped skin.…”
Section: Ultraviolet Irradiationmentioning
confidence: 97%
“…However, tape stripping did not increase ALAHE‐induced PpIX fluorescence outside the application area (van den Akker et al ., ). In an in vitro study van den Akker also showed that penetration of ALA and the ALA esters was higher, 100‐ and 200‐fold respectively, through tape‐stripped rather than through normal mouse skin (van den Akker et al ., ).…”
Section: Mechnical Damage: Tape Stripping Abrasionmentioning
confidence: 99%